Indigenous information as tool for consolidating and promoting natural resources conservation in Igbo-speaking communities of Southeast Nigeria (2016)
Prior to modernization, indigenous peoples had strong mechanisms for communicating, regulating and managing natural resources endowments for their survival and development. Modern knowledge and information management systems have not sufficiently improved conservation and natural resource development especially among rural folks. This study was conducted in Igbo-speaking rural communities of Obowo LGA of Imo State in SE Nigeria to elicit information on conventional and indigenous information dissemination and exchange methods on natural resource conservation with the view to identifying the impacts of indigenous information methods on resource conservation. Data obtained from in-depth Interview (IDIs) sessions with key stakeholders within the locality revealed the availability of medicinal plants, arable lands and rivers/streams occurring in relatively high abundance as attested to by 71.0%, 56.0% and 48.0% of the respondents, respectively. Also, rural people access information about natural resources and environment through a variety of media/platforms (both formal and indigenous). Fractional ranking showed that the top five (5) indigenous information media were oral tradition (1.5), local authority leadership structure (1.5), village assembly (2), story-telling (4) and individual enquiry (5.5). Local authority structure among other indigenous information media manifested the highest positive influence (31.3%) on conservation/consolidation of identified resource. Specifically, local authority was the source of information rivers/streams (63.2%) and arable lands (56.0%) conservation. It is therefore imperative for governments and international agencies to see information media mix especially through recognizable local institutional channels (local authorities) as veritable instruments for sustaining and promoting sustainable development especially of natural resources at different community, national and global levels.